THE ROLE OF LESSON PLAN AS AN EFFORT TO IMPROVE THE QUALITY OF TEACHERS IN TEACHING ENGLISH - Iskandar, Yusuf (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
This study is aimed to (1), determine the role of teaching English. (2) prove that the use of lesson plan  give effect toward improvement of teacher’s quality in teaching, especially for teaching English. This study is a classroom action. The subject of this study is English teachers of SMA Negeri 5 Garut. Techniques of collecting datas are by using observation, interviews and documentations. The result of observation and interview with the English teachers in a public senior high school in Garut West Java that all English teachers have arranged and used  the lesson plan, and obtained data, from the six English teachers who do not understand about the role of lesson plan are only 2 persons, while 4 other English teachers have understood the role of lesson plan in teaching English. But, in improving and implementation, it is constrained by several factors as I explain in the discussion. But, in practice, English teachers will effort with existing abilities and collaborate with  other teachers to keep contributing  the best services to students in accordance with syllabus and English teaching plan and teach based on the lesson plan that accordance to condition and student’s characters in the present and the future.So, from this study, we can take  a conclusion that a lesson plan  gives big effect in improving English teachers qualities especially teachers in n a public senior high school in Garut and others in general.   Keywords: lesson plan, teacher’s quality, teaching English